A STUDY ON MEANING AND VALUES OF MONEY PAPER AND PRAYER PAPER IN DEATH RITES OF INDONESIAN CHINESE - Rebecca Milka Natalia Basuki (Jurnal Sosioteknologi, 2016)
There are three important events in human's life, such as births, marriages and deaths. Death rites are one of the most important in Chinese culture. In Chinese culture, death rites symbolize a new start for a new life, connecting the lives and the deceased, giving pledge to ancestors, and involved rich visuality in the process. In a death rite, there are a lot of elements and artifacts with high esthetics, art values, and good craftmanship. But in the end, they are not only functioned as decorations, but they have spesific functions and meanings, which usually not realized by the people.This research focused on money papers and prayer paper in Chinese's death rites. There are three rites locations observed to look at the differences and cultural acculturations between Chinese culture and local culture. Research problems are to find out how those elements are used in the rites, their meanings, values and functions in death rites. The research are using visual ethnography as a method and visual anthropology approach in order to gain deeper understanding of research objects' roles in death rites. The results showed their roles as important parts of death rites, and as mediums of communication. They delivered immanent communication and transcendental communication. They are also functioned to help human being to understand their humanities. In the end, money paper and prayer paper are not just requirements for rites or decorations, but meaningful to entire human life. Keywords: Death Rites, Money Paper, Prayer Paper, Visual Ethnography